MOBILE COMMUNICATIONS DEVELOPMENT - Сініцин, Р. Б.; Кольченко, Л. В.; Кудренко, С. О. (Science-based technologies, 2009)
Mobile communication is the fastest growing field in the telecommunications industry. This article discusses the history, present state, and future of cellular radio networks. Prospective of 2G cellular radio networks transfer to 3G ones is also regarded in this article